PROSES PENJUALAN JASA TRANSPORTASI PADA PT BIMA SEPAJA ABADI JAKARTA - Kurnia Elma Tiara; Metya Lutviani (POLITEKNIK LP3I JAKARTA, 2024)
Transportation services are a system of transporting or moving goods from the place where the transportation activity begins or the starting place to the place where the transportation activity ends. The purpose of this research is to determine the Sales Process of Transportation Services at PT Bima Sepaja Abadi. The research method used is to conduct a direct study of the company, namely through observation, interviews and literature studies by studying various forms of written materials. The steps used are to discuss the process of selling transportation services. The discovery of obstacles that occur in the reporting process and their solutions can provide input that can help the company to carry out transaction reporting administration procedures that are more effective and efficient than before, so that reporting administration can run according to company procedures.